2020
DOI: 10.1155/2020/6401082
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Incident Clearance Time Prediction and Influencing Factor Analysis Using Extreme Gradient Boosting Model

Abstract: Accurate prediction and reliable significant factor analysis of incident clearance time are two main objects of traffic incident management (TIM) system, as it could help to relieve traffic congestion caused by traffic incidents. This study applies the extreme gradient boosting machine algorithm (XGBoost) to predict incident clearance time on freeway and analyze the significant factors of clearance time. The XGBoost integrates the superiority of statistical and machine learning methods, which can flexibly deal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…1 above) and indicate which model performs better than the others do in predicting the bank loans in our specification. MSE and MAPE are commonly employed as predictive indicators to compare alternative models' prediction performance (Alpaydin 2014;Tang et al 2020). The results in Table 2 indicate that not many differences exist in the predictive performance of the employed algorithms.…”
Section: Evaluation Of the Models By Their Prediction Performancementioning
confidence: 99%
“…1 above) and indicate which model performs better than the others do in predicting the bank loans in our specification. MSE and MAPE are commonly employed as predictive indicators to compare alternative models' prediction performance (Alpaydin 2014;Tang et al 2020). The results in Table 2 indicate that not many differences exist in the predictive performance of the employed algorithms.…”
Section: Evaluation Of the Models By Their Prediction Performancementioning
confidence: 99%
“…e reason for choosing this site is the heavy traffic demand and frequent incident-induced traffic congestion events. Additionally, in previous studies, Tang et al [32] used the data source to analyze the influence of explanatory variables and examine the prediction performance of the proposed model. And Hou et al [45] analyzed the time-varying effects of significant variables based on this dataset.…”
Section: Data Descriptionmentioning
confidence: 99%
“…To overcome the imbalanced traffic incident duration data problem of the single-tree-based method, Ma et al [30] found that the gradient boosting decision tree model has a superior performance in model interpretation and prediction accuracy to conventional DT models [31]. Also based on traditional DT models, the extreme gradient boosting machine algorithm was applied to analyze and predict the clearance time data [32,33]. However, the machine learning models are usually not capable of interpreting the mechanism between estimator and explanatory variables.…”
Section: Introductionmentioning
confidence: 99%
“…For ascariasis, the selected model was the Performance Clustered eXtreme Gradient Boosted Trees Regressor, while the eXtreme Gradient Boosted Trees Regressor with Early Stopping (Gamma Loss) was chosen for both enterobiasis and CE. Extreme gradient boosting is an efficient version of gradient boosting ensemble machine learning algorithm, which has been optimized and tweaked for fast runtimes and predictive accuracy [79].…”
Section: Time Series Forecasting For 2019 and 2020mentioning
confidence: 99%